2022
DOI: 10.3390/molecules27175628
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lycium barbarum L. Polysaccharides on Vascular Retinopathy: An Insight Review

Abstract: Vascular retinopathy is a pathological change in the retina caused by ocular or systemic vascular diseases that can lead to blurred vision and the risk of blindness. Lycium barbarum polysaccharides (LBPs) are extracted from the fruit of traditional Chinese medicine, L. barbarum. They have strong biological activities, including immune regulation, antioxidation, and neuroprotection, and have been shown to improve vision in numerous studies. At present, there is no systematic literature review of LBPs on vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 117 publications
0
8
0
Order By: Relevance
“…In all these extraction methods, the similar underlying principle is the degradation of the cell wall under certain conditions without affecting the polysaccharide activity [ 25 ]. Each extraction method has its pros and cons [ 26 ]. When selecting specific methods, it is essential to weigh the high extraction rate and biological activity of LBPs.…”
Section: The Natural Existence and Acquisition Of Lbps In Daily Lifementioning
confidence: 99%
See 2 more Smart Citations
“…In all these extraction methods, the similar underlying principle is the degradation of the cell wall under certain conditions without affecting the polysaccharide activity [ 25 ]. Each extraction method has its pros and cons [ 26 ]. When selecting specific methods, it is essential to weigh the high extraction rate and biological activity of LBPs.…”
Section: The Natural Existence and Acquisition Of Lbps In Daily Lifementioning
confidence: 99%
“…The LBPs are highly branched, and the main chain is a (1→6) Galp-connected galactose [ 30 ]. It is the complex structure of a polysaccharide that determines its biological activity [ 26 ].…”
Section: The Natural Existence and Acquisition Of Lbps In Daily Lifementioning
confidence: 99%
See 1 more Smart Citation
“…The fruit, root bark and leaves of Lycium barbarum are widely used as food and pharmaceutical additives [32], and contains rich chemical components [33]. A large number of studies have shown that it has a variety of favorable biological effects in patients with diabetes [32,34], impaired reproductive systems [35,36], eye diseases [37,38], cardiovascular diseases [39,40] and cancers [41,42]. Lycium barbarum polysaccharide (LBP), the main active component of Lycium barbarum, has been shown to possess anti-oxidation, anti-inflammatory, anti-tumor and anti-aging properties [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…The biological properties of wolfberries have been also largely reported and reviewed. For instance, when performing a browse search in the Web of Science platform in November 2022 using the following key words "Lycium barbarum review", and restricting for year 2022 only, it is possible to find a large number of review papers that have in their scope of analysis this species, as well as its antioxidant, anti-inflammatory, anti-aging, hypoglycemic and hypolipidemic activities, modulation of gut microbiota, neuroprotective, neuroprotective effects on retinal ganglion cells, immunomodulatory, positive effects on cognitive impairment, anti-fatigue effect, hepatoprotective, and anti-tumor effect [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. The role of the plant polysaccharides, including that of L. barbarum, in drug delivery system in tumor treatment, targeted therapy, and wound healing was also reviewed and discussed [63].…”
Section: Introductionmentioning
confidence: 99%